(untitled) (מכאן, 2017)
The dangers of identity politics are currently a burning theoretical and political issue in Israel because of its role in justifying racism and fascism. This article looks at this with reference to Carol Jacobs’ exemplary discussion of Jane Campion’s film, The Piano (1993). In her article Jacobs, refusing to subjugate the interpretive act to as tructuralist binary of identities, and hence of meanings, proposes a reading of the political and moral dialectics of identity politics. Beyond Paul de Man’s resistance to mimetic interpretation that focuses on effects, Jacobs employs a method that allows for a moral stance by distorting and suspending the interpretation of the text’s array of signifiers. Identity politics is not the final word in addressing oppression and disaster. Jacobs’ interpretation of the film points to a tenet reached through a state of emergency in which viewers are pulled out of what she refers to as "blindanalphabetism"; it is a reading that bypasses the problematic nature of a rhetoric of political struggle based on solid identities. Jacobs’ reading does not hide behind the apolitical world of organized and institutionalized identities, but deals with the rhetoric of political struggle. By distancing oneself from the text its figurativeness stands out, allowing one to hear its otherness. Jacobs’ feminism goes beyond the demand for women’s liberation and avoids reproducing oppressive male authority by means of a slow reading that distorts the rhetoric of oppression. She suggests turning what is disturbing, unpredictable and strange into the focus of the interpretive process, thus enabling an impulse toward political action based on the film’s performance. There is no question that Jacobs’ critique on the lack of flexible of the identity politics is crucial. But there are many cases when an immediate response towards an eruption of violence could be too prolonged. Publication of such an important article in the current State of Israel where the hopeless is exposed frequently to an immediate cruel violence can actually teach us how dangerous can be any postponement in its recommendation of a moral judgment.